1999
DOI: 10.1046/j.1365-2109.1999.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased ability to compete for food by growth hormone-transgenic coho salmonOncorhynchus kisutch(Walbaum)

Abstract: In salmonids, growth hormone (GH) stimulates growth, appetite and the ability to compete for food. This study tested the hypothesis that increased GH levels in GH‐transgenic coho salmon Oncorhynchus kisutch (Walbaum) increase competitive ability through higher feeding motivation. The transgenic strain of salmon used contained a gene construct consisting of the sockeye metallothionein‐B promoter fused to the type 1 growth gene coding region. The transgenic animals (mean size = 250 g) were F1 individuals. In six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 15 publications
7
86
0
1
Order By: Relevance
“…Previous studies have reported significant differences in morphology between the GHtransgenic salmonids and the controls [32][33][34][35]. Ostenfeld et al [36] and Lee et al [31] suggested that changes in body shape were responsible for reduced critical swimming speeds (Ucrit) of GH-transgenic salmonids.…”
Section: Viability Of Transgenic Fishmentioning
confidence: 99%
“…Previous studies have reported significant differences in morphology between the GHtransgenic salmonids and the controls [32][33][34][35]. Ostenfeld et al [36] and Lee et al [31] suggested that changes in body shape were responsible for reduced critical swimming speeds (Ucrit) of GH-transgenic salmonids.…”
Section: Viability Of Transgenic Fishmentioning
confidence: 99%
“…Our results suggested that the altered GH secretion pattern may change the mRNA expression levels of hypothalamic orexigenic factor AgRP I in TG common carp. The constant overexpression of GH transgene can result in increased food intake and feeding behavior (Abrahams and Sutterlin, 1999;Devlin et al, 1999;Duan et al, 2009Duan et al, , 2011Sundstrom et al, 2003), and GH can also regulate food intake by acting on the feeding control centre of the central nervous system (CNS) (Bohlooly et al, 2005). Therefore, we speculate that the constant high levels of hypothalamic and serum GH may have a direct or indirect impact on the feeding regulation centre in the hypothalamus, thereby enhancing appetite and feeding motivation.…”
Section: Gh and Hypothalamic Feeding Regulationmentioning
confidence: 99%
“…Similarly, elevated GH in transgenic salmon induced heightened feeding motivation, increased food intake and feeding behavior (Abrahams and Sutterlin, 1999;Devlin et al, 1999;Sundstrom et al, 2003). In our previous study, we also found that TG common carp consumed more food during competition with normal common carp of the same size, and that this was associated with higher social status and enhanced feeding motivation (Duan et al, 2011).…”
Section: Gh Increased Food Intakementioning
confidence: 99%
See 1 more Smart Citation
“…These transgenic fish overexpress GH and require enhanced feed consumption to achieve the increased growth rates (29). Observations under laboratory conditions have shown GH transgenic fish to be more competitive (30), less discriminate in choosing prey (31), less affected by predator presence when making foraging decisions (32), more likely to attack novel prey (31), and better at using lower-quality food (29) compared with genetically wild relatives. In the natural environment, such physiological and behavioral alterations have the potential to directly influence not only conspecifics through increased competition for food but also prey populations and previously unaffected species through increased predation.…”
mentioning
confidence: 99%